Predictive models forecast relationships of apelin-13 concentrations with UCP1 in WAT and BAT, and UCP3 in muscle - Tekin, Suat; Erden, Yavuz; Sandal, Suleyman; Etem, Ebru; Colak, Cemil (Wiley-Blackwell, 2015)
[Abstract Not Available]